Is the Cost of Corporate Debt Affected by the Volume and Intensity of Carbon Emissions? - Sukoco, Y. Djoko; Gumanti, Tatang Ary; Ariyani, Vivi (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to examine the impact of carbon risk on the debt costs of non-financial companies listed on the Indonesia Stock Exchange (idx) from 2017 to 2023. Carbon risk is proxied by carbon emission volume and carbon emission intensity, which are considered more closely aligned with the government's goal of achieving net-zero emissions by 2060. The hypothesis is tested using fixed-effects regression on a 1,023-unbalanced panel dataset. The results show that before the implementation of the Financial Services Authority Regulation (POJK) No. 51 of 2017, carbon risk had a significant negative impact on corporate debt costs. Following the implementation of the regulation, the negative effect of carbon risk on the cost of debt weakened and became statistically insignificant positive direction. This indicates that creditors have begun to internalize the carbon risk in their assessment of corporate borrowing costs.